Characteristics and factors affecting surface and shallow landslides in West Java, Indonesia - Yulia Amirul Fata; Hendrayanto Hendrayanto; Budi Kuncahyo; Erizal Erizal; Suria Darma Tarigan (Brawijaya University, 2022)
Bogor, Cianjur, and Sukabumi areas of West Java Province, Indonesia, are vulnerable landslide areas. This study analyzes the landslide characteristic and the factors affecting landslides. The analysis was carried out on 148 landslides from 415 of 2018-2020 landslides, which were selected purposively by considering the heterogeneity of soil, geology, slope classes, land use type, and accessibility of landslide locations. Landslide characteristics and factors affecting landslides were analyzed using frequency analysis and binary logistic regression. The results showed that the most dominant characteristics of surface and shallow landslides were the landslides characterized by slopes >45%, Quaternary geological period, Andisol soil type, agriculture land use type, the occurrence of rain, and absence of earthquake. The dominant factors affecting surface and shallow landslides are human activities in land use, soil properties, steep-very steep slopes, Inceptisol and Entisol soil orders, young rocks (Quaternary geological period), rainfall events, and high earthquake magnitude.